NiO / Ag / ZnIn2S4 heterojunction nanosheet array, preparation method thereof and room-temperature gas sensor
By designing NIO/AG/Znin2S4 heterogeneous nanoma array and adopting a sandwich -type S -type ternary heterogeneous structure, the existing semiconductor gas sensor work at high temperature and light at high temperature. Perform high -sensitivity and high -selective testing of triamine gas.
Patent Information
- Application Number
- CN202411934423.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-26
AI Technical Summary
Existing semiconductor gas sensors need to be heated and driven at high temperatures, with high power consumption and high risk of use in flammable and explosive atmospheres. The development of photoexcited semiconductor gas sensors is limited due to the high photogenerated carrier recombination rate and low visible light absorption efficiency. .
Design a NIO/AG/Znin2S4 heterogeneous nanoma tablet array, adopts sandwich -type S -type ternary heterogeneous structure, introduces precious metal AG between two semiconductor components of S -type heterogeneous knots to build a sandwich The meta -heterogeneous knot is to promote the absorption of visible light at the high -efficiency separation of optical carriers at the interface and enhance the semiconductor material.
Achieve high -sensitivity and high selective testing of totoramine gas at room temperature, showing a response to 100 PPM triamine as high as 30, with excellent selectivity and low detection limit for 447 PPB. The manufacturing process of gas sensors.
Smart Images

Figure CN119349655A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nano material heterojunction, and specifically relates to a NiO / Ag / ZnIn 2 S 4 Heterojunction nanosheet array, preparation method thereof and room temperature gas sensor. Background Art
[0002] Semiconductor gas sensors based on metal oxides can effectively detect and monitor environmental gases. However, traditional semiconductor gas sensors generally need to be heated and driven at high temperatures to work, which greatly increases the power consumption of the sensor and the risk of using it in flammable and explosive atmospheres. The excitation of semiconductor gas-sensitive materials by photons can enhance the gas-sensitive response of semiconductor materials by generating abundant photogenerated carriers and surface reactive species. This method has been shown to be promising to replace traditional thermal excitation and significantly reduce the operating temperature of the sensor. However, the extremely high photogenerated carrier recombination rate and low visible light absorption efficiency of common semiconductor gas-sensitive materials greatly limit the improvement of gas-sensitive performance under photoexcitation, which has become the two major bottlenecks for the further development of photoexcitation semiconductor gas sensors.
[0003] To address the problem of high recombination rate of photogenerated carriers in semiconductor gas-sensitive materials, designing semiconductor heterojunctions is currently the most common strategy. Compared with the three traditional types of semiconductor heterojunctions, the new S-type heterojunction discovered in recent years has enhanced photogenerated carrier separation efficiency due to its unique photogenerated carrier transfer mechanism, while maintaining the oxidation / reduction ability of photogenerated carriers to the maximum extent. The unique advantages of the S-type heterojunction have led to a large number of studies in the field of photocatalysis (including photocatalytic hydrogen production, degradation of water pollutants, carbon dioxide reduction, etc.) in recent years. However, so far, research on S-type heterojunctions in the field of semiconductor gas sensors has received little attention. The unique advantages of the S-type heterojunction are very promising to solve the problem of high recombination rate of photogenerated carriers in photoexcited semiconductor gas sensors. In addition, in order to address the problem of low visible light absorption efficiency of semiconductor gas-sensitive materials, by reasonably selecting narrow-bandgap semiconductor components with good visible light absorption effect in the S-type heterojunction to replace traditional wide-bandgap semiconductor gas-sensitive materials (such as ZnO, SnO 2 and TiO 2 ) is also expected to be solved to a large extent. In conclusion, there is an urgent need to experimentally develop new S-type heterojunctions for use in the field of photoexcitation-type semiconductor gas sensors.
[0004] For the S-type heterojunction constructed by directly compounding two semiconductors, recent studies have found that the competition of directional migrating carriers and the unstable contact interface caused by lattice structure mismatch often pose great challenges to the effective separation of photogenerated carriers at the interface. Therefore, it is urgent to solve this problem, which is expected to further accelerate the development of light-excited semiconductor gas sensors. Summary of the invention
[0005] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art and provide a NiO / Ag / ZnIn 2 S 4 Heterojunction nanosheet array and its preparation method and application, specifically an S-type sandwich structure NiO / Ag / ZnIn 2 S 4 Heterojunction nanosheet array, preparation method thereof and room temperature gas sensor.
[0006] In order to solve the competition of directional migration carriers in the S-type heterojunction of the direct composite structure of two semiconductors and the unstable contact interface problem caused by lattice structure mismatch, the applicant has found through research that if a noble metal is introduced between the two semiconductor components of the S-type heterojunction to construct a sandwich-type ternary heterojunction, this problem can be well solved. On the one hand, noble metals can act as electron traps and media, greatly promoting the efficient separation of photogenerated carriers at the interface. On the other hand, the surface plasmon resonance (SPR) effect of noble metals can further enhance the absorption of visible light by semiconductor materials and promote the generation of photogenerated carriers. In short, the introduction of noble metals in S-type heterojunctions is expected to further accelerate the development of photoexcited semiconductor gas sensors.
[0007] In the present invention, the applicant designed a novel sandwich NiO / Ag / ZnIn 2 S 4 The ternary S-type heterojunction nanosheet array is composed of a nickel oxide porous nanosheet array grown in situ on the surface of a commercial alumina gas sensor substrate, an Ag nanoparticle intermediate layer, and a two-dimensional ultra-thin ZnIn wrapped on the outermost layer. 2 S 4 Thanks to the synergistic effect of the unique photogenerated carrier transfer mechanism of the S-type heterojunction, the SPR effect of the precious metal Ag nanoparticles, and the design of the porous nanoarray structure, the sensor can achieve high sensitivity and high selectivity detection of triethylamine gas at room temperature under the excitation of low-power white LED light (0.06W), showing a response of up to 30 (R g / R a ), with excellent selectivity and a low limit of detection (LOD) of 447 ppb. Importantly, the sandwich NiO / Ag / ZnIn2 S 4 The nanoarray is grown in situ on the surface of a commercial alumina gas-sensitive substrate, which greatly simplifies the complex manufacturing process of traditional semiconductor gas sensors (including powder synthesis, slurry preparation, slurry coating, thick film drying, etc.), while effectively avoiding a series of problems in the film formation process of semiconductor materials, including agglomeration, structural damage and insufficient electrical contact. Based on the first-principles calculation and spectral characterization of the system (including in situ infrared), the applicant conducted an in-depth study on the gas-sensing mechanism of this ternary S-type heterojunction. This study provides a new idea for synergistically improving the gas-sensing performance of photoexcited semiconductor gas sensors through the S-type mechanism and the noble metal SPR effect, and will provide important experimental and theoretical guidance for the material design of photoexcited semiconductor gas sensors.
[0008] The technical solution of the present invention is as follows: The first aspect of the present invention provides a NiO / Ag / ZnIn 2 S 4 Heterojunction nanosheet array, comprising a substrate and NiO / Ag / ZnIn in-situ grown on the surface of the substrate 2 S 4 Heterojunction nanosheet arrays, the NiO / Ag / ZnIn 2 S 4 Heterojunction arrays composed of NiO porous nanosheets, Ag nanoparticles and ZnIn 2 S 4 Nanosheet composition; The NiO porous nanosheets are in a vertically staggered array structure, the Ag nanoparticles are evenly dispersed on the surface of the NiO porous nanosheets, and the ZnIn 2 S 4 Wrapping the NiO porous nanosheet.
[0009] The present invention constructs a semiconductor gas sensor array in situ on a gas-sensitive substrate. Since the sensing layer is an array constructed in situ on the gas-sensitive substrate, this not only avoids a series of problems caused by the thick film formation process in the traditional process, but also greatly simplifies the manufacturing cost of the device and makes the miniaturization of the device possible. In addition, due to the close combination between the sensing film and the gas-sensitive substrate, the consistency and reliability of the sensor are also guaranteed. Most importantly, since the sensor array is usually porous and has a large specific surface area, this is very conducive to the diffusion of the target gas and the surface gas sensor reaction.
[0010] As a further preferred embodiment, the substrate is Al 2 O 3 Gas sensitive substrate.
[0011] The above Al 2O 3 The gas-sensitive substrate is a commercially available flat Al 2 O 3 Gas sensing substrate. The substrate is made of cheap and readily available Al 2 O 3 The surface has two pairs of Pt interdigital electrodes, one pair is the heating electrode, and the other pair is the resistance signal collection electrode. Substrate heating and resistance signal collection are very convenient, and the two pairs of electrodes will not interfere with each other. NiO / Ag / ZnIn 2 S 4 Heterojunction nanosheet arrays are used as a new type of gas-sensitive sensing layer for surface gas adsorption and gas-sensitive reaction.
[0012] As a further preferred embodiment, the lateral size of the NiO porous nanosheet is 50 nm to 150 nm, the size of the Ag nanoparticle is 1 nm to 20 nm, and the size of the ZnIn 2 S 4 The thickness of the nanosheet wrapping is 10 nm~50 nm.
[0013] As a further preferred embodiment, the loading amount of the Ag nanoparticles is 2 wt% to 3 wt%; The NiO / Ag / ZnIn 2 S 4 The specific surface area is 90m 2 / g~100m 2 / g.
[0014] The second aspect of the present invention provides the NiO / Ag / ZnIn 2 S 4 The method for preparing a heterojunction nanosheet array comprises the following steps: A NiO porous nanosheet is grown on the surface of a substrate by a hydrothermal method combined with an annealing treatment, wherein the NiO porous nanosheet is a vertically staggered growth array structure; Modifying Ag nanoparticles on the surface of the NiO porous nanosheets by photodeposition to obtain an intermediate product NiO / Ag nanosheet array; ZnIn was grown on the surface of the NiO / Ag nanosheet array by a water bath method. 2 S 4 Nanosheets, the final product NiO / Ag / ZnIn 2 S 4 Heterojunction nanosheet arrays.
[0015] As a further preferred embodiment, the step of growing NiO porous nanosheets on the substrate surface by a hydrothermal method combined with annealing treatment specifically includes: Nickel nitrate, ammonium fluoride and urea are dissolved in water and stirred to obtain a reaction solution. Then, a substrate is added to the reaction solution for a hydrothermal reaction. The reaction time is 4 h~9 h and the reaction temperature is 80 ℃~120 ℃. After the reaction, the substrate is washed, dried and then annealed. The annealing temperature is 450 ℃~650 ℃ and the annealing time is 1 h~3 h. After the annealing treatment, NiO porous nanosheets are obtained.
[0016] When the reaction temperature is 100 ℃ ~ 150 ℃, the alkaline source urea begins to decompose slowly. If the temperature is too low, urea cannot decompose to produce OH - , Ni(OH) 2 If the temperature is too high, urea will decompose too quickly and ammonium fluoride will not be able to adjust the pH value of the reaction system through buffering. When the annealing temperature is 450℃~600℃, the purpose of annealing is to convert Ni(OH) 2 Converted into NiO, this process mainly involves decomposition and dehydration. If the temperature is too low, Ni(OH) 2 It is impossible to completely decompose and dehydrate into NiO; if the temperature is too high, the NiO nanosheets will continue to grow, causing the nanosheets to become thicker and sticky.
[0017] As a further preferred embodiment, the molar ratio of nickel nitrate, ammonium fluoride and urea is 1:3-5:5-7. Urea is an alkali source, and its decomposition can produce OH - , the metal Ni ions and OH in nickel nitrate - Combine to form Ni(OH) 2 As a strong acid and weak base salt, ammonium fluoride can effectively control the pH value of the reaction system, thereby achieving Ni(OH) 2 The control of nucleation growth leads to the formation of ultra-thin nanosheet morphology. Through a large number of experimental studies, it was found that the optimal molar ratio of nickel nitrate, ammonium fluoride and urea is 1:4:5. Too much or too little urea and ammonium fluoride are not conducive to the formation of the optimal nanosheet structure.
[0018] As a further preferred embodiment, modifying Ag nanoparticles on the surface of the NiO porous nanosheets by photodeposition specifically comprises the following steps: Pour the silver nitrate solution into water and mix well to obtain a mixed solution; The NiO porous nanosheet is immersed in the mixed solution to perform a photodeposition reaction, and a mercury lamp is used to irradiate the NiO porous nanosheet. After the reaction is completed, the NiO porous nanosheet is washed and dried to obtain a NiO / Ag nanosheet array.
[0019] As a further preferred embodiment, the power of the mercury lamp is 600 W to 1200 W, and the irradiation time is 0.1 h to 1.5 h; The molar ratio of silver nitrate to nickel oxide is 1:200-400; more preferably, the optimal molar ratio of silver nitrate to nickel oxide is 1:400.
[0020] As a further preferred embodiment, ZnIn is grown on the surface of the NiO / Ag nanosheet array by a water bath method. 2 S 4 The nanosheet specifically includes the following steps: Adjust the pH value of water to 1-3 with nitric acid, add glycerol, and ultrasonicate to obtain a solution; Dissolve zinc chloride, indium chloride and thioacetamide in the solution, mix and stir to obtain a reaction solution, then immerse the NiO / Ag porous nanosheet in the reaction solution for water bath reaction, maintain the temperature at 20°C~100°C, react for 1 h~4 h, wash and dry the product after the reaction, and finally obtain NiO / Ag / ZnIn 2 S 4 Heterojunction nanosheet arrays.
[0021] As a further preferred embodiment, the concentration of the nitric acid is 0.5 mol / L to 2 mol / L, and the volume ratio of the glycerol to water is 1 to 3:15 to 35; The molar ratio of the zinc chloride, indium chloride and thioacetamide is 1:1-3:2-5.
[0022] A third aspect of the present invention provides a room temperature gas sensor, comprising the above-mentioned NiO / Ag / ZnIn 2 S 4 Heterojunction nanosheet arrays.
[0023] As a further preferred embodiment, the room temperature gas sensor is a gas sensor for detecting triethylamine.
[0024] NiO / Ag / ZnIn of the present invention 2 S 4 The heterojunction nanosheet array is applied in room temperature gas sensor and has high selective detection of triethylamine at room temperature under white light excitation.
[0025] The present invention has at least one of the following beneficial effects: The preparation process of the present invention is simple and the cost is low. The NiO / Ag / ZnIn prepared by the present invention 2 S 4 The heterojunction nanosheet array has good heterojunction interface contact, and NiO / Ag / ZnIn 2 S 4The presence of Ag nanoparticles in the heterojunction nanosheet arrays greatly promotes the 2 S 4 The electron transfer between ZnIn 2 S 4 The wrapping of NiO / Ag / ZnIn increases the specific surface area of the material. 2 S 4 Heterojunction nanosheet arrays can be used in room-temperature gas sensors, specifically for room-temperature highly selective detection of triethylamine under white light excitation. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The NiO / Ag / ZnIn prepared in Example 1 is shown. 2 S 4 Heterojunction nanosheet arrays, comparative samples, pure NiO, and pure ZnIn 2 S 4 X-ray diffraction (XRD) pattern; Figure 2 The NiO / Ag / ZnIn prepared in Example 1 is shown. 2 S 4 Scanning electron microscope (SEM) images, transmission electron microscope (TEM) images and element distribution maps of heterojunction nanosheet arrays and comparative sample NiO; (a) and (b) are SEM images of NiO nanosheet arrays at different resolutions; (c) and (d) are TEM images of NiO / Ag at different resolutions; (e) and (f) are TEM images of NiO / ZnIn at different resolutions. 2 S 4 Morphological characterization; (g) and (h) are NiO / Ag / ZnIn at different resolutions. 2 S 4 SEM characterization of NiO / Ag / ZnIn at different resolutions; (i), (j) and (k) 2 S 4 TEM images and high-resolution TEM images; (l), (m), (n), (o), (p), (q) and (r) are NiO / Ag / ZnIn 2 S 4 Element mapping image; Figure 3 The NiO / Ag / ZnIn prepared in Example 1 is shown. 2 S 4 Nitrogen adsorption / desorption isotherms and corresponding pore size distribution curves of heterojunction nanosheet arrays and comparative samples; (a) NiO; (b) NiO / Ag; (c) NiO / ZnIn 2 S 4; (d) NiO / Ag / ZnIn 2 S 4 .
[0027] Figure 4 The NiO / Ag / ZnIn prepared in Example 1 is shown. 2 S 4 X-ray photoelectron spectroscopy (XPS) images of heterojunction nanosheet arrays and comparative samples; among them, (a) XPS spectrum of Ni element; (b) XPS spectrum of O element; (c) XPS spectrum of Ag element: (d) XPS spectrum of Zn element; (e) XPS spectrum of In element; (f) XPS spectrum of S element.
[0028] Figure 5 The NiO / Ag / ZnIn prepared in Example 1 is shown. 2 S 4 In situ x-ray photoelectron spectroscopy (in situ XPS) images of heterojunction nanosheet arrays and comparison samples; among them, (a) peak position shift of O element; (b) peak position shift of Zn element; (c) peak position shift of In element; (d) peak position shift of S element.
[0029] Figure 6 The NiO / Ag / ZnIn prepared in Example 1 is shown. 2 S 4 Dynamic gas-sensitive response of heterojunction nanosheet arrays and comparative samples to 100 ppm triethylamine under room temperature white light conditions; (a) NiO / Ag / ZnIn 2 S 4 ; (b) NiO / ZnIn 2 S 4 ; (c) NiO / Ag; (d) NiO.
[0030] Figure 7 The NiO / Ag / ZnIn prepared in Example 1 is shown. 2 S 4 Dynamic gas-sensitive response of heterojunction nanosheet arrays and comparative samples to different concentrations of triethylamine under room temperature white light conditions; (a) NiO / Ag / ZnIn 2 S 4 ; (b) NiO / ZnIn 2 S 4 ; (c) NiO / Ag; (d) NiO. DETAILED DESCRIPTION
[0031] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] Example 1 A NiO / Ag / ZnIn 2 S 4 A heterojunction nanosheet array, the preparation method of which comprises the following steps: Step 1: First, commercial flat Al 2 O 3 The gas-sensitive substrate (produced by Wuhan Huachuang Ruike Technology Co., Ltd.) was repeatedly washed in deionized water and anhydrous ethanol and then dried for use; Step 2: Nickel nitrate (Ni(NO 3 ) 2 6H 2 O), ammonium fluoride (NH 4 F) and urea (CH 4 N 2 O) was added into a polytetrafluoroethylene autoclave in a molar ratio of 1:4:5, and then deionized water was added until the inner volume filling degree was 72%, and magnetic stirring was continued for 0.2 hours to obtain a reaction solution; the washed commercial flat-plate Al 2 O 3 The gas-sensitive substrate was subjected to hydrothermal reaction, the reaction temperature was set to 100 °C, and the reaction time was 8 hours. After the reaction, the commercial flat Al 2 O 3 The gas-sensitive substrate was washed and dried, and then annealed in a muffle furnace at a temperature of 500 °C for 2 hours to obtain a NiO porous nanosheet array. Step 3: Add silver nitrate (AgNO 3 ) solution (0.01 mmol) was poured into 40 mL of deionized water and mixed to obtain a mixed solution; then the NiO porous nanosheet array was immersed in the mixed solution for photodeposition reaction, the power of the mercury lamp was set to 1000 W to irradiate the NiO porous nanosheet array, and the reaction time was 30 minutes. After the reaction, the NiO porous nanosheet array was washed and dried to obtain a NiO / Ag porous nanosheet array.
[0033] Step 4: Adjust the pH value of deionized water (20 mL) to 2.5 with 1 mol / L nitric acid, add 3 mL glycerol, and ultrasonicate for 1 hour. Dissolve zinc chloride, indium chloride, and thioacetamide in the above solution at a molar ratio of 1:1:2, mix well, and stir for 1 hour to obtain a reaction solution. Then immerse the NiO / Ag porous nanosheet array in the reaction solution for water bath reaction. Use a water bath to maintain the temperature of the reaction solution at 80°C for 2 hours. After the reaction, NiO / Ag / ZnIn 2 S 4 The heterojunction nanosheet array is washed and dried to finally obtain NiO / Ag / ZnIn 2 S 4 Heterojunction nanosheet arrays.
[0034] Example 2 A NiO / Ag / ZnIn 2 S 4 A heterojunction nanosheet array, the preparation method of which comprises the following steps: Step 1: First, commercial flat Al 2 O 3 The gas-sensitive substrate (produced by Wuhan Huachuang Ruike Technology Co., Ltd.) was repeatedly washed in deionized water and anhydrous ethanol and then dried for use; Step 2: Nickel nitrate (Ni(NO 3 ) 2 6H 2 O), ammonium fluoride (NH 4 F) and urea (CH 4 N 2 O) was added into a polytetrafluoroethylene autoclave in a molar ratio of 1:4:6, and then deionized water was added until the inner volume filling degree was 65%, and magnetic stirring was continued for 0.5 hours to obtain a reaction solution; the washed commercial flat-plate Al 2 O 3 The gas-sensitive substrate was subjected to hydrothermal reaction, the reaction temperature was set to 110 °C, and the reaction time was 10 hours. After the reaction, the commercial flat Al 2 O 3 The gas-sensitive substrate was washed and dried, and then annealed in a muffle furnace at a temperature of 400 °C for 2 hours to obtain a NiO porous nanosheet array. Step 3: Add silver nitrate (AgNO 3) solution (0.02 mmol) was poured into 50 mL of deionized water and mixed to obtain a mixed solution; then the NiO porous nanosheet array was immersed in the mixed solution for photodeposition reaction, the power of the mercury lamp was set to 800 W to irradiate the NiO porous nanosheet array, and the reaction time was 45 minutes. After the reaction, the NiO porous nanosheet array was washed and dried to obtain a NiO / Ag porous nanosheet array.
[0035] Step 4: Adjust the pH value of deionized water (35 mL) to 3.0 with 2.5 mol / L nitric acid, add 1 mL glycerol, and ultrasonicate for 1 hour. Dissolve zinc chloride, indium chloride, and thioacetamide in the above solution at a molar ratio of 1:2:2, mix well, and stir for 1 hour to obtain a reaction solution. Then immerse the NiO / Ag porous nanosheet array in the reaction solution for water bath reaction. Use a water bath to maintain the temperature of the reaction solution at 100°C for 1.5 hours. After the reaction, 2 S 4 The heterojunction nanosheet array is washed and dried to finally obtain NiO / Ag / ZnIn 2 S 4 Heterojunction nanosheet arrays.
[0036] Example 3 A NiO / Ag / ZnIn 2 S 4 A heterojunction nanosheet array, the preparation method of which comprises the following steps: Step 1: First, commercial flat Al 2 O 3 The gas-sensitive substrate (produced by Wuhan Huachuang Ruike Technology Co., Ltd.) was repeatedly washed in deionized water and anhydrous ethanol and then dried for use; Step 2: Nickel nitrate (Ni(NO 3 ) 2 6H 2 O), ammonium fluoride (NH 4 F) and urea (CH 4 N 2 O) was added into a polytetrafluoroethylene autoclave in a molar ratio of 1:4:5, and then deionized water was added until the inner volume filling degree was 80%, and magnetic stirring was continued for 1 hour to obtain a reaction solution; the washed commercial flat-plate Al 2 O 3 The gas-sensitive substrate was subjected to hydrothermal reaction, the reaction temperature was set to 80 °C, and the reaction time was 15 hours. After the reaction, the commercial flat Al 2 O 3The gas-sensitive substrate was washed and dried, and then annealed in a muffle furnace at a temperature of 550 °C for 2 hours to obtain a NiO porous nanosheet array. Step 3: Add silver nitrate (AgNO 3 ) solution (0.03 mmol) was poured into 35 mL of deionized water and mixed. Then, the NiO porous nanosheet array was immersed in the mixed solution for photodeposition reaction. The power of the mercury lamp was set to 1100 W to irradiate the NiO porous nanosheet array. The reaction time was 25 min. After the reaction, the NiO porous nanosheet array was washed and dried to obtain a NiO / Ag porous nanosheet array.
[0037] Step 4. Adjust the pH value of deionized water (15 mL) to 2.0 with 2 mol / L nitric acid, add 5 mL glycerol, and ultrasonicate for 0.5 hours. Dissolve zinc chloride, indium chloride, and thioacetamide in the above solution at a molar ratio of 1:3:4, mix well, and stir for 1 hour to obtain a reaction solution. Then immerse the NiO / Ag porous nanosheet array in the reaction solution for water bath reaction. Use a water bath to maintain the temperature of the reaction solution at 130°C for 2 hours. After the reaction, NiO / Ag / ZnIn 2 S 4 The heterojunction nanosheet array is washed and dried to finally obtain NiO / Ag / ZnIn 2 S 4 Heterojunction nanosheet arrays.
[0038] Comparative Example 1 Only NiO nanosheets are prepared, and the preparation method is as follows: Nickel nitrate (Ni(NO 3 ) 2 6H 2 O), ammonium fluoride (NH 4 F) and urea (CH 4 N 2 O) was added into a polytetrafluoroethylene autoclave in a molar ratio of 1:4:5, and then deionized water was added until the inner volume filling degree was 72%, and magnetic stirring was continued for 0.2 hours to obtain a reaction solution; the washed commercial flat-plate Al 2 O 3 The gas-sensitive substrate was subjected to hydrothermal reaction, the reaction temperature was set to 100 °C, and the reaction time was 8 hours. After the reaction, the commercial flat Al 2 O 3 The gas-sensitive substrate was washed and dried, and then annealed in a muffle furnace. The annealing temperature was set at 500 °C and the annealing time was set at 2 hours to obtain a NiO nanosheet array.
[0039] Comparative Example 2 Only NiO / Ag porous nanosheet arrays are prepared, and the preparation method is as follows: Nickel nitrate (Ni(NO 3 ) 2 6H 2 O), ammonium fluoride (NH 4 F) and urea (CH 4 N 2 O) was added into a polytetrafluoroethylene autoclave in a molar ratio of 1:4:5, and then deionized water was added until the inner volume filling degree was 72%, and magnetic stirring was continued for 0.2 hours to obtain a reaction solution; the washed commercial flat-plate Al 2 O 3 The gas-sensitive substrate was subjected to hydrothermal reaction, the reaction temperature was set to 100 °C, and the reaction time was 8 hours. After the reaction, the commercial flat Al 2 O 3 The gas-sensitive substrate was washed and dried, and then annealed in a muffle furnace. The annealing temperature was set at 500 °C and the annealing time was set at 2 hours to obtain a NiO porous nanosheet array.
[0040] Silver nitrate (AgNO 3 ) solution (0.01 mmol) was poured into 40 mL of deionized water and mixed to obtain a mixed solution; then the NiO porous nanosheet array was immersed in the mixed solution for photodeposition reaction, the power of the mercury lamp was set to 1000 W to irradiate the NiO porous nanosheet array, and the reaction time was 30 minutes. After the reaction, the NiO porous nanosheet array was washed and dried to obtain a NiO / Ag nanosheet array.
[0041] Comparative Example 3 Only NiO / ZnIn 2 S 4 Materials and preparation methods are as follows: Nickel nitrate (Ni(NO 3 ) 2 6H 2 O), ammonium fluoride (NH 4 F) and urea (CH 4 N 2 O) was added into a polytetrafluoroethylene autoclave in a molar ratio of 1:4:5, and then deionized water was added until the inner volume filling degree was 72%, and magnetic stirring was continued for 0.2 hours to obtain a reaction solution; the washed commercial flat-plate Al 2 O 3 The gas-sensitive substrate was subjected to hydrothermal reaction, the reaction temperature was set to 100 °C, and the reaction time was 8 hours. After the reaction, the commercial flat Al 2 O 3The gas-sensitive substrate was washed and dried, and then annealed in a muffle furnace. The annealing temperature was set at 500 °C and the annealing time was set at 2 hours to obtain a NiO porous nanosheet array.
[0042] The pH value of the water was adjusted to 2.5 with 1 mol / L nitric acid, and 3 mL of glycerol was added and ultrasonicated for 0.5 h. Zinc chloride, indium chloride and thioacetamide were dissolved in the above solution at a molar ratio of 1:1:2, mixed and stirred for 1 h to obtain a reaction solution, and then the NiO porous nanosheet array was immersed in the reaction solution for water bath reaction, and the temperature of the reaction solution was maintained at 80 °C in a water bath pot for 2 h. After the reaction, the NiO / ZnIn 2 S 4 The heterojunction nanosheet array is washed and dried to finally obtain NiO / ZnIn 2 S 4 Heterojunction nanosheet arrays.
[0043] Figure 1 NiO / Ag / ZnIn in Example 1 2 S 4 Heterojunction array and comparative samples NiO nanosheets (Comparative Example 1), NiO / Ag porous nanosheet arrays (Comparative Example 2), NiO / ZnIn 2 S 4 Materials (Comparative Example 3), pure NiO and pure ZnIn 2 S 4 X-ray diffraction (XRD) patterns of pure NiO, see JCPDS No. 47-1049 for the XRD patterns of pure ZnIn 2 S 4 For the XRD pattern, please refer to the Joint Committee on Powder Diffraction Standards No. JCPDS No. 65-2023. It can be seen that the comparative sample NiO nanosheet (Comparative Example 1) is pure NiO, while the composite NiO / Ag / ZnIn 2 S 4 Heterojunction arrays with both NiO and ZnIn 2 S 4 The phase of NiO / Ag and NiO / Ag / ZnIn 2 S 4 No characteristic diffraction peaks of Ag were observed in the XRD patterns of the two composite samples, mainly due to the low loading content of Ag particles (loading amount was 2.4 wt%) and the fact that Ag nanoparticles were used as an intermediate layer by ZnIn 2 S 4 The coating also masks its diffraction peaks to a large extent.
[0044] Figure 2 NiO / Ag / ZnIn in Example 1 2 S 4 Heterojunction array and comparative samples NiO, NiO / Ag and NiO / ZnIn 2 S 4 Scanning electron microscope (SEM) photos, transmission electron microscope (TEM) photos and element distribution maps. The morphology and microstructure of the prepared samples can be observed by SEM and TEM. Figure 2 (a) and Figure 2 As shown in (b) in Figure 2, these two pictures show the morphology of NiO nanosheet arrays, which grow vertically and staggered on the surface of the gas-sensitive substrate, and the surface of the NiO nanosheets is smooth and flat, with a thickness of about 50 nanometers. Figure 2 (d) in the figure is a TEM morphology photograph of the NiO / Ag sample. Since the Ag particles are small, their morphology cannot be observed in the low-magnification SEM, so TEM and high-resolution TEM (high-resolution transmission electron microscope HRTEM) are used to characterize them. From the TEM photos, it can be seen that there are a large number of evenly distributed mesopores on the surface of the nanosheets, and black Ag nanoparticles with a size of 1nm-20nm are evenly dispersed on the surface of the NiO nanosheets. With the help of HRTEM, the high-resolution lattice fringes of the particles can be clearly observed. Its crystal plane spacing is 0.241nm, which can be attributed to the (111) crystal plane of metallic Ag. Figure 2 (e) and Figure 2 (f) is NiO / ZnIn 2 S 4 From the morphological characterization, it can be observed that a large amount of ZnIn is evenly coated on the surface of NiO nanosheets. 2 S 4 Nanosheets form a good heterogeneous core-shell structure. NiO / Ag / ZnIn 2 S 4 SEM characterization of Figure 2 (g) and Figure 2 As shown in (h), its overall morphology is similar to that of NiO / ZnIn 2 S 4 Not much difference, ZnIn 2 S 4 The nanosheets uniformly wrapped the NiO nanosheets and Ag nanoparticles to form a sandwich heterojunction. Figure 2 (i) Figure 2 (j) and Figure 2 The (k) in the graph is NiO / Ag / ZnIn respectively. 2 S 4TEM image and high-resolution TEM image. From the TEM image, we can clearly see that ZnIn 2 S 4 Nanosheets cover the surface of NiO and Ag nanoparticles. The HRTEM image shows three different sets of lattice fringes. The lattice spacing of 0.241 nm in the upper left corner corresponds to the (111) crystal plane of Ag, the lattice spacing of 0.243 nm in the middle matches the (111) crystal plane of NiO, and the lattice spacing of 0.317 nm in the lower right corner matches the (111) crystal plane of ZnIn 2 S 4 The above results show that a good heterogeneous interface contact is formed between the three. In addition, Figure 2 (l) Figure 2 (m) Figure 2 (n) Figure 2 (o) in Figure 2 (p) Figure 2 (q) and Figure 2 (r) is NiO / Ag / ZnIn 2 S 4 Element mapping image. It can be seen that the spatial distribution of Ni, O, Ag, Zn, In, and S is uniform, which is consistent with its morphological characteristics.
[0045] In order to further study the specific surface area and pore structure of the samples, the applicant tested NiO, NiO / Ag, NiO / ZnIn 2 S 4 and NiO / Ag / ZnIn 2 S 4 The nitrogen adsorption-desorption isotherm, such as Figure 3 As shown. All four samples show type IV isotherms and H3 hysteresis loops, indicating the presence of abundant mesopores, which is consistent with their morphological characteristics. According to calculations, NiO, NiO / Ag, NiO / ZnIn 2 S 4 and NiO / Ag / ZnIn 2 S 4 The specific surface areas are 86.1123m 2 / g, 95.5484m 2 / g, 90.3461m 2 / g and 95.7655m 2 / g. Generally speaking, a large specific surface area and porous structure will provide more active sites for gas sensing reactions, thus contributing to the improvement of performance.
[0046] By measuring NiO, NiO / Ag, NiO / ZnIn 2 S 4and NiO / Ag / ZnIn 2 S 4 The chemical composition and state of NiO were studied by X-ray photoelectron spectroscopy (XPS) spectra. Figure 4 (a) to Figure 4 (f) show the X-ray photoelectron spectroscopy (XPS) spectra of Ni, O, Ag, Zn, In, and S in the four samples. Figure 4 (a) shows that for pure NiO, Ni 2p 3 / 2 The main peaks are located at 854.37 eV and 856.03 eV, respectively, and the satellite peak is located at 861.53 eV. Ni 2p 1 / 2 The peaks are located at 872.01eV and 873.92 eV, respectively, and the satellite peak is located at 879.76 eV. The XPS spectra peak positions of the four samples Ni are basically consistent. For the O element in Figure 4 (b), the peak at 529.88eV can be attributed to chemically adsorbed oxygen, while the O1s peak of 531.62eV can be attributed to lattice oxygen. Comparing the O1s peak positions of the four samples, it can be seen that from the monolithic NiO to the binary NiO / Ag and NiO / ZnIn 2 S 4 Then to the ternary NiO / Ag / ZnIn 2 S 4 , the proportion of chemically adsorbed oxygen gradually increased, and the overall peak position moved toward the direction of low binding energy, indicating that ZnIn 2 S 4 Transfer electrons to NiO, and the O element in NiO gains electrons. Figure 4 (c) is the XPS spectrum of Ag. The peak positions of Ag in the two materials can be well attributed to the peaks of metallic Ag. Figure 4 (d)-Figure 4 (f) are respectively ZnIn 2 S 4 The peaks of the three elements Zn, In and S are basically similar to those reported in the literature. The Zn 2p XPS spectrum shows two obvious peaks at 1022.0eV and 1045.1eV, and the peak positions of Zn in the two samples are basically the same. However, the ternary NiO / Ag / ZnIn 2 S 4 The peaks of In and S in NiO / ZnIn 2 S 4 All shift to the right, this is because ZnIn 2 S 4 In the process of transferring electrons to NiO, S and In elements lose electrons, the binding energy increases, and the presence of Ag acts as a bridge for electron transfer, which greatly promotes this electron transfer process. Therefore, compared with NiO / ZnIn 2 S 4 , center sample NiO / Ag / ZnIn 2 S4 The peak position shifts further toward the direction of increasing binding energy.
[0047] In addition, if Figure 5 As shown in the figure, the peak shifts of O, S and In in the in-situ XPS spectrum are opposite to those in the absence of light. 2 S 4 After forming a heterojunction, ZnIn 2 S 4 The electrons flow to NiO with a lower Fermi level and form a ZnIn 2 S 4 Pointing to the built-in electric field of NiO. Under visible light excitation, NiO and ZnIn 2 S 4 The electrons in their respective valence bands transition to the conduction band and are transferred from NiO to ZnIn under the action of the built-in electric field. 2 S 4 Therefore, the situation of gaining and losing electrons is just the opposite of normal conditions. The O element loses electrons, the binding energy increases, and the S and In elements gain electrons, and the binding energy decreases. This confirms that NiO / Ag / ZnIn 2 S 4 The electron transfer process of the heterojunction conforms to the S-type separation mechanism.
[0048] On this basis, the applicant used the prepared nanoarray to detect triethylamine at room temperature. 2 S 4 The response to triethylamine (100 ppm) was very limited (<4), as shown in Figure 6 (b) Figure 6 (c) Figure 6 However, NiO / Ag / ZnIn 2 S 4 Under low power (0.06W) white LED light excitation, it exhibits excellent room temperature gas sensitivity to triethylamine. Figure 6 As shown in (a), in the eight cycles of the stability test, each time 100ppm of triethylamine was introduced, the gas sensor's response value to the target gas increased by an average of about 30 times, and eventually returned to the original response value. In the detection experiment of triethylamine at different concentrations under room temperature white light excitation, Figure 7 As shown in (a), NiO / Ag / ZnIn 2 S 4 It also showed that it could produce gas-sensitive response to triethylamine in a wide concentration range. Figure 7 As shown in (d) in Figure 2, the gas sensing performance of NiO alone to triethylamine is low (less than 2). Figure 7 (b) and Figure 7 As shown in (c), NiO / Ag and NiO / ZnIn 2 S 4 The gas sensitivity to triethylamine is also low.
[0049] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A NiO / Ag / ZnIn2S4 heterojunction nanosheet array, characterized in that: It comprises a substrate and a NiO / Ag / ZnIn2S4 heterojunction nanosheet array in-situ grown on the surface of the substrate, wherein the NiO / Ag / ZnIn2S4 heterojunction array is composed of NiO porous nanosheets, Ag nanoparticles and ZnIn2S4 nanosheets; The NiO porous nanosheets are in a vertically staggered array structure, the Ag nanoparticles are evenly dispersed on the surface of the NiO porous nanosheets, and the ZnIn2S4 wraps the NiO porous nanosheets.
2. The NiO / Ag / ZnIn2S4 heterojunction nanosheet array according to claim 1, characterized in that: The lateral size of the NiO porous nanosheet is 50 nm to 150 nm, the size of the Ag nanoparticle is 1 nm to 20 nm, and the thickness of the ZnIn2S4 nanosheet package is 10 nm to 50 nm; The substrate is an Al2O3 gas-sensitive substrate.
3. The NiO / Ag / ZnIn2S4 heterojunction nanosheet array according to claim 1, characterized in that: The loading amount of the Ag nanoparticles is 2 wt% to 3 wt%; The specific surface area of NiO / Ag / ZnIn2S4 is 90m 2 / g~100m 2 / g.
4. The method for preparing the NiO / Ag / ZnIn2S4 heterojunction nanosheet array according to any one of claims 1 to 3, characterized in that: The following steps are involved: A NiO porous nanosheet is grown on the surface of a substrate by a hydrothermal method combined with an annealing treatment, wherein the NiO porous nanosheet is a vertically staggered growth array structure; Modifying Ag nanoparticles on the surface of the NiO porous nanosheets by photodeposition to obtain an intermediate product NiO / Ag nanosheet array; A water bath method is used to grow ZnIn2S4 nanosheets on the surface of the NiO / Ag nanosheet array to obtain a final product, a NiO / Ag / ZnIn2S4 heterojunction nanosheet array.
5. The preparation method according to claim 4, characterized in that: The steps of growing NiO porous nanosheets on the substrate surface by using a hydrothermal method combined with annealing treatment specifically include: Nickel nitrate, ammonium fluoride and urea are dissolved in water and stirred to obtain a reaction solution, and then a substrate is added to the reaction solution for a hydrothermal reaction, the reaction time is 4 h~9 h, the reaction temperature is 80 ℃~120 ℃, after the reaction is completed, the substrate is washed, dried, and then annealed, the annealing temperature is 450 ℃~650 ℃, the annealing time is 1 h~3 h, and after the annealing treatment, NiO porous nanosheets are obtained; Wherein, the molar ratio of the nickel nitrate, ammonium fluoride and urea is 1:3-5:5-7.
6. The preparation method according to claim 4, characterized in that: Modifying Ag nanoparticles on the surface of the NiO porous nanosheets by photodeposition specifically comprises the following steps: Pour the silver nitrate solution into water and mix well to obtain a mixed solution; The NiO porous nanosheet is immersed in the mixed solution to perform a photodeposition reaction, and a mercury lamp is used to irradiate the NiO porous nanosheet. After the reaction is completed, the NiO porous nanosheet is washed and dried to obtain a NiO / Ag nanosheet array.
7. The preparation method according to claim 6, characterized in that: The power of the mercury lamp is 600 W to 1200 W, and the irradiation time is 0.1 h to 1.5 h; The molar ratio of the silver nitrate to the nickel oxide is 1:200-400.
8. The preparation method according to claim 4, characterized in that: The method of growing ZnIn2S4 nanosheets on the surface of the NiO / Ag nanosheet array by a water bath method specifically comprises the following steps: Adjust the pH value of water to 1-3 with nitric acid, add glycerol, and ultrasonicate to obtain a solution; Zinc chloride, indium chloride and thioacetamide are dissolved in the solution, mixed and stirred to obtain a reaction solution, and then the NiO / Ag porous nanosheet is immersed in the reaction solution for a water bath reaction, the temperature is maintained at 20°C~100°C, and the reaction is carried out for 1 h~4 h. After the reaction is completed, the product is washed and dried to finally obtain a NiO / Ag / ZnIn2S4 heterojunction nanosheet array.
9. The preparation method according to claim 8, characterized in that: The concentration of the nitric acid is 0.5 mol / L to 2 mol / L, and the volume ratio of the glycerol to water is 1 to 3:15 to 35; The molar ratio of the zinc chloride, indium chloride and thioacetamide is 1:1-3:2-5.
10. A room temperature gas sensor, characterized in that: It comprises the NiO / Ag / ZnIn2S4 heterojunction nanosheet array as described in any one of claims 1 to 3.
Citation Information
Patent Citations
Precious metal / zinc indium sulfide / titanium dioxide nano heterostructure photocatalyst and preparation method thereof
CN104923259A
Beta-catenin photoelectric immunoassay method based on Z-type tungsten trioxide-nanogold-indium zinc sulfide heterojunction
CN112213499A
Ternary Au / ZnIn2S4 / NaTaO3 nanocube composite photocatalyst as well as preparation method and application thereof
CN114558591A
Photocatalyst as well as preparation method and application thereof
CN114588888A
Triethylamine gas sensor based on porous flower-shaped CdS / CdIn2S4 heterojunction composite sensitive material and preparation method
CN114894854A
Cited By
Silver / transition oxometallate heterojunction nano material, preparation method and application
CN120055259A
Bi2WO6 / ZnIn2S4 / Ag ternary hierarchical heterojunction as well as preparation method and application thereof
CN121990609A